'Registrar in charge shifts': Learning how to run a busy emergency department. (11th January 2013) - Craig, Simon; Dowling, Jonathan
Abstract Objectives In Australasia, emergency registrars usually gain experience 'running' an ED overnight – without supervision. This paper describes the introduction of FACEM‐supervised daytime 'registrar in charge' (RIC) shifts into a tertiary adult ED over a 6 month period. Methods Each registrar was allocated at least one RIC shift during their 13 week ED term. Structured questionnaires gathered data regarding the educational impact of the shifts, any adverse effects on departmental function, changes to work practices, and perceptions of teaching and learning. Data were analysed using thematic analysis. Results During the study period, 16 senior ED registrars were rostered for 26 RIC shifts. Questionnaires were completed by 16/16 registrars and 13/16 emergency physicians. The RIC shifts were viewed positively by the emergency registrars – 93% reported useful feedback, felt that the shifts provided a good insight into their workplace behaviour, and that they should be rolled out across other departments. FACEMs were also positive in their evaluation, and reported little negative impact on departmental function. Major themes identified by both registrars and emergency physicians included communication skills, knowledge and experience, delegation, professionalism and organisational skills. Additional themes that were more prominent in FACEM responses included multitasking, dealing with interruptions, managing patient flow and being aware of the whole department. Conclusions RIC shifts are a feasible and acceptable method to teach running the floor in the ED. Further study should assess impact on patient outcomes.